Decolonial translation in Daniel Caño’s Stxaj no’anima / Oración Salvaje - Olen, Amy (The Journal of Specialised Translation, 2015)
Guatemalan, Maya-Q'anjob'al poet Daniel Caño critiques the legacy of spiritual coloniality for Guatemalan Mayas in his 2011, dual Q'anjob'al-Castilian book of poetry Stxaj no' anima / Oración Salvaje, or in English, Savage Prayer. In this essay, I argue that his poetry asserts a Maya indigenous critique of the imposition of Catholicism on Maya spiritual belief systems and the attempted erasure of Maya spirituality in Guatemala through assimilative practices. A key tool of assimilation for Catholic missionaries is translation. With a close reading of Caño's poems "With the Bible in Hand," "You Are Not Baptised," and "Savage Prayer," I signal the ways in which Caño's texts challenge the assimilative translations of missionary Catholicism, and Western characterisations of Maya spirituality as 'barbarism.' I argue that Caño crafts his challenges to missionary Catholicism by delineating central tenets of Maya spiritual belief systems, particularly the interconnectedness of humans and nature, and the relation between oral tradition, spirituality and the body. His work juxtaposes Maya and Western epistemologies through what I call 'decolonial translations.' Through his 'decolonial translations,' Caño critiques Guatemalan spiritual coloniality as articulated in the translation of Catholic spiritual doctrine into indigenous languages. Caño's critique thus contests the efficacy of Spanish missionary practices aimed at Maya assimilation in Guatemala.